Pessanha correspondent: the melancholic’s mask - Frasson Fusco, Felipe (2023)
The paper aims the reading of a part, specially the correspondence with Carlos Amaro, of the Portuguese poet Camilo Pessanha’s (1867-1926) epistolary work. In 1908, his brother Manuel was put into a psychiatric institution in Porto, and since then this brother’s shadow haunts the poet’s correspondence. The self-pity tone increases, along with an uprising melancholic discourse. We seek to analyze such discourse, relying both on references on the epistolary writing, Diaz (2016) and Haroche-Bouzinac (2016), as well as Starobinski (2016) on melancholy. We conclude that Pessanha frequently builds his self-image as a victim of melancholy, connecting it specially to the brotherly figure.